The effect of a health promotion program on the wellness behavior and self-esteem of women, and the influence of self-esteem upon behavior change - Pierce, Erlene (My University, 1982)
This research examined change in self-esteem and wellness behavior among women ages 34 to 75 following a health promotion program. It also examined the effect of self-esteem upon the pursuit of wellness behavior. Qs consisted of 35 members of the Lutheran Hospital Auxiliary, La Crosse, Wisconsin who completed three inventories as pre- and pos ttest assessment. The Health Risk Analysis and Wellness Index assessed behavior change. The Coopersmith Self-esteem Inventory measured self-esteem. High and low selfesteem groups were assigned based upon the normal range established for this population. It was derived from pretest scores of the Self-esteem Inventory.
Keywords: Women - Health and hygiene; Health behavior; Self-esteem; Women - Health programs